Investment Commitments in the Middle East and North Africa Reached a Peak Level in 2007 - Izaguirre, Ada Karina; Perard, Edouard (World Bank, Washington, DC, 2012)
Investment commitments to infrastructure projects with private participation in the Middle East and North Africa grew by 7 percent to US$12.8 billion in 2007, the highest level since 1990, according to just-released data from the private participation in infrastructure project database. The region accounted for 8 percent of the year's total investment commitments to developing countries. Investment commitments in the region were driven mainly by projects implemented in previous years. Projects reaching financial closure in 1990-2006 attracted US$7.8 billion, while the 13 new projects implemented in 2007 accounted for US$5.1 billion. Investment in physical assets grew by 35 percent to US$8.3 billion, the highest level ever. Payments to governments (such as divestiture revenues and spectrum or concession fees) fell from the highest level reached (US$5.3 billion, in 2006) to US$4.6 billion, about 36 percent of annual investment.